Genetic variation at major histocompatibility complex loci in Neotoma albigula (white-throated woodrat) potential clues to the evolution of North American arenaviruses. - Hoss, Sarah G. (My University, 2012)
The major histocompatibility complex Mhc is an important component of vertebrate immune systems, and as such, genetic analysis of Mhc loci have been shown to provide information on susceptibility to viral infection. Neotoma albigula (white-throated woodrat) are naturally associated with at least 3 arenaviruses, and are considered the putative host species for all 3 viruses. Strains of arenaviruses can cause severe febrile diseases in humans and are considered a serious health risk where human-rodent interactions are common. The association of N. albigula with at least 3 viruses suggests a significant co-evolutionary history between the host and virus. In this study, Mhc loci were screened to detect genetic variation among N. albigula populations in Arizona. This was done to test the prediction that levels of genetic variation at Mhc loci in N. albigula will correlate with specific arenaviral strains. The results have indicated moderate genetic variation among groups but almost no correlation with viral data.--Abstract.
Keywords: White-throated wood rat; Major histocompatibility complex; Viruses